Anti -TNFα agents in preventing the postoperative recurrence of Crohn's disease: Do they still play a role in the biological era?. (2nd November 2021) - Liu, Caiguang; Li, Na; Zhan, Shukai; Tian, Zhenyi; Wu, Dongxuan; Li, Tong; Zeng, Zhirong; Zhuang, Xiaojun
ABSTRACT: Background: Approximately half of patients with Crohn's disease (CD) may inevitably receive surgical intervention as the disease progress. However, about 75% of CD patients will experience postoperative recurrence (POR). Biologics are appealing alternatives for the prevention of POR; however, it is still unclear which biological agents are more efficient. This meta-analysis aimed to investigate the efficacy of biologics for POR prevention and to compare the superiority of different biologics. Methods: We conducted a thorough search of online databases and screened for studies on the efficacy of biologics in preventing POR (clinical, endoscopic, or histological) that were published until January 2021. The results were presented as forest plots and odds ratios (ORs) with 95% confidence intervals (CIs). Results: We included 26 studies with 2, 136 participants. Overall, biologics were more efficient over non-biological treatments in preventing endoscopic, severe endoscopic, and clinical POR without increasing the frequency of adverse events. Among the various types of biologics, anti-TNFα agents were better than vedolizumab in preventing endoscopic POR. Moreover, infliximab had a similar curative effect to adalimumab in preventing endoscopic, severe endoscopic, and clinical recurrence. Conclusion: Biologics, especially anti-TNFα agents, still play a vital role in preventing POR in the biological era.